ENHANCING ENTREPRENEURIAL MOTIVATION OF CULINARY MSME OWNERS IN KEBON MANGGIS, JAKARTA TIMUR - Fujianti, Lailah; Prakoso, Roy; Indriati, Petiana; Crenata, Rachel Marsilea (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The service aims to increase the knowledge of Kebon Manggis MSME players about the need to maintain motivation and entrepreneurial spirit to advance and maintain business sustainability and be able to face challenges or obstacles in running a business. This service was carried out using the lecture method. The implementation of the service has four stages: initial survey, preparation, implementation, and evaluation of implementation. This service was carried out on 19 July 2023 and was attended by 19 MSME actors. The evaluation results show that there is an increase in knowledge before and after the implementation of the service.